Searching for clues for eighteen years: Deciphering the ecological determinants of Cryptococcus gattii on Vancouver Island, British Columbia. (19th May 2017) - Acheson, Emily Sohanna; Galanis, Eleni; Bartlett, Karen; Mak, Sunny; Klinkenberg, Brian
Abstract: Cryptococcus gattii emerged on Vancouver Island in 1999 for unknown reasons, causing human and animal fatalities and illness. The apparent emergence of this fungus in another temperate area, this time in the Pacific Northwest, suggests the fungus may have expanded its ecological niche. Yet studies that directly examine the potential roles of climatic and land use changes on C. gattii are still lacking. We aim to summarize the existing global literature on the ecology of C. gattii, with particular focus on the gap in knowledge surrounding the potential effects of climatic and land use changes. We systematically reviewed English peer-reviewed literature on the ecological determinants of C. gattii . We included studies published from January 1970 through June 2016 and identified 56 relevant studies for our review. We identified environmental isolations of C. gattii from 18 countries, spanning 72 separate regions across six continents. Fifty-three tree species were associated with C. gattii, spanning 10 climate classifications and 36 terrestrial ecoregions. No studies directly tested the potential effects of climatic changes (including climatic oscillations and global climate change) on C. gattii, while only one study directly assessed those of land use change. To improve model predictions of current and future distributions of C. gattii, more focus is needed on the potential effects of climatic and land use changes to help decrease the public health risk. The apparent emergence of C. gattii in British Columbia is also an opportunity to explore the factors behind emerging infectious diseases in Canada and elsewhere.